Load analyser using conservative power theory - Marafão, Fernando Pinhabel [UNESP]; Souza, Wesley Angelino de; Liberado, Eduardo Verri; Silva, Luiz Carlos Pereira da; Paredes, Helmo Kelis Morales [UNESP] (My University, 2013)
This paper deals with the analysis and application of novel conformity factors, defined by means of the Conservative Power Theory (CPT), for the purpose of load analysis and characterization. Basically, such factors are able to describe the influence of different load characteristic on the power factor calculation and they are valid under generic load and supply voltage conditions. Moreover, the development of a flexible smart-meter prototype has been described and used to the experimental validation of all power components and conformity factors considered on the paper.

W artykule zaprezentowano analizę i zastosowanie nowego współczynnika zgodności zdefiniowanego na podstawie Teorii Zachowania Mocy CPT. Współczynnik zastosowano do analizy obciążeń iich wpływu na współczynnik mocy. Opisano też nową koncepcję miernika typu smart.-meter.
Analiza obciążeń przy wykorzystaniu teorii zachowania mocy CPT
Keywords: Conservative power theory; Load analyser; Power meter; Power quality; Power theories; Smart meter; Teoria zachowania mocy CPT; Analiza obciążeń; Smart meter